Carbon nanotubes: a novel innovation as food supplements and biosensing for food safety - Masood, Maazallah; Albayouk, Tala; Saleh, Na'il; El-Shazly, Mohamed; El-Nashar, Heba A. S. (Frontiers in Nutrition, 2024)
Recently, nanotechnology has emerged as an extensively growing field. Several important fabricated products including Carbon nanotubes (CNTs) are of great importance and hold significance in several industrial sectors, mainly food industry. Recent developments have come up with methodologies for the prevention of health complications like lack of adequate nutrition in our diet.This review delves deeper into the details of the food supplementation techniques and how CNTs function in this regard. This review includes the challenges in using CNTs for food applications and their future prospects in the industry. Food shortage has become a global issue and limiting food resources put an additional burden on the farmers for growing crops. Apart from quantity, quality should also be taken into consideration and new ways should be developed for increasing nutritional value of food items. Food supplementation has several complications due to the biologically active compounds and reaction in the in vivo environment, CNTs can play a crucial role in countering this problem through the supplementation of food by various processes including; nanoencapsulation and nanobiofortification thus stimulating crop growth and seed germination rates. CNTs also hold a key position in biosensing and diagnostic application for either the quality control of the food supplements or the detection of contagions like toxins, chemicals, dyes, pesticides, pathogens, additives, and preservatives. Detection such pathogens can help in attaining global food security goal and better production and provision of food resources. The data used in the current review was collected up to date as of March 31, 2024 and contains the best of our knowledge. Data collection was performed from various reliable and authentic literatures comprising PubMed database, Springer Link, Scopus, Wiley Online, Web of Science, ScienceDirect, and Google Scholar. Research related to commercially available CNTs has been added for the readers seeking additional information on the use of CNTs in various economic sectors.